If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + u)(2u + -7) = 0 Reorder the terms: (6 + u)(-7 + 2u) = 0 Multiply (6 + u) * (-7 + 2u) (6(-7 + 2u) + u(-7 + 2u)) = 0 ((-7 * 6 + 2u * 6) + u(-7 + 2u)) = 0 ((-42 + 12u) + u(-7 + 2u)) = 0 (-42 + 12u + (-7 * u + 2u * u)) = 0 (-42 + 12u + (-7u + 2u2)) = 0 Combine like terms: 12u + -7u = 5u (-42 + 5u + 2u2) = 0 Solving -42 + 5u + 2u2 = 0 Solving for variable 'u'. Factor a trinomial. (-6 + -1u)(7 + -2u) = 0Subproblem 1
Set the factor '(-6 + -1u)' equal to zero and attempt to solve: Simplifying -6 + -1u = 0 Solving -6 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1u = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1u = 0 + 6 -1u = 0 + 6 Combine like terms: 0 + 6 = 6 -1u = 6 Divide each side by '-1'. u = -6 Simplifying u = -6Subproblem 2
Set the factor '(7 + -2u)' equal to zero and attempt to solve: Simplifying 7 + -2u = 0 Solving 7 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2u = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2u = 0 + -7 -2u = 0 + -7 Combine like terms: 0 + -7 = -7 -2u = -7 Divide each side by '-2'. u = 3.5 Simplifying u = 3.5Solution
u = {-6, 3.5}
| 0.09xX=161.14 | | 3x-3x=24 | | x^2+3x^2=4x^2 | | 5/4-7/3x | | 6y+2y=7y+9 | | 3/8b=24 | | 3(x+1.83)=2x | | 0.09xX=121.10 | | -11/9x=-1/5 | | (10x-2)=55+63 | | (3x+15)=(4x-10) | | -3/10y=-6 | | 6w+5=9w+2 | | (2x+5)=33 | | 6x+5y+2x-2y= | | .16(y-6)+.02y=.08y-.7 | | 3w+4=2w+11 | | 0.6y+6.5=0.5(9+y) | | 6p=91 | | 6x+5y+2x= | | 28-2x=34 | | (6x)+(4x-3)=46 | | -4.5x+1.1=-16.9 | | 4(2x-8)-7=4(x-4)+5 | | .7x+4.2=.6x+1.4 | | 7x+6x(4)=-93 | | 14x-(6x-3)=59 | | 2(4z+1)-7=59 | | 6[2-(3+4x)]-2x=-8+2(1-13x) | | (2x-2)+(5x-7)= | | X-25/100 | | 2x^2-12x-12= |